Space, urban borders, and political imagination in Buenos Aires - Grimson, Alejandro (2016)
The present article analyzes the relationship between urban borders and political imagination among popular sectors in contemporary Buenos Aires. On the basis of 100 qualitative interviews with leaders of social organizations from the 4 major regions of the city, different ways of comprehending and acting in particular spaces will be compared, and the role of urban borders and their relation to political processes examined. For this, the article focuses on the intersection between class, race, and ethnicity in the historical construction of urban borders in Buenos Aires. By identifying the tendency to naturalize and reproduce objectified social oppositions in a physical space as categories for perceiving and evaluating the social space, the article points up the relevance of local political matrices and neighborhood boundaries in the structuring of social bonds, local organizations, and political imagination.